A General and Facile Synthesis of Novel Polysubstituted Quinazolin‐4(3H)‐ones. (28th January 2013) - Xin, Minhang; Gao, Ying; Xiang, Hua; Chen, Dong; He, Yi; You, Qidong
<x xml:space="preserve">Abstract</x> A simple and efficient approach to synthesize novel polysubstituted quinazolin‐4(3H)‐ones has been developed, and the key step is a sequential procedure involved iron‐mediated reduction and acid‐catalytic cyclization. The present method provides a convenient and practical strategy for the synthesis of quinazolin‐4(3H)‐one derivatives.